Response Surface Optimization and In-vitro Evaluation of Sustained Release Topical Insulin Liposomal Spray for Wound Healing - Marwa H. S. Dawoud, Ghada E. Yassin & , Dalia M. Ghorab, Nadia M. Morsi (Journal of Applied Pharmaceutical Science, 2018)
Chronic wounds are considered a major health care concern, that represents a life-threatening problem worldwide. Insulin has proven its great efficiency as a wound healing agent, especially with diabetic ulcers. However; insulin suffers degradation at the application site due to proteases, moreover; when wounds are painful the patient fails to apply any remedy frequently. In the present study, insulin has been formulated as a spray in liposomes, which protects it at the wound area and sustains its release and thus reducing the application frequency, furthermore; the spray reducing the direct contact of the applicator with the skin, thus, reducing the probability of infection. The full-factorial design has been applied in the preparation optimization of liposomes, where the effects of the cholesterol, method of preparation and sonication have been tested on the particle size and the entrapment efficiency. The present study shows how the thin film hydration method in the absence of cholesterol and sonication were the best conditions for insulin. liposomal formulation, that satisfies the target of the study. Liposomes showed a sustained release of insulin up to 24 hours and were successfully formulated into a spray dosage form. In conclusion, topical insulin liposomal spray offers a protective method from insulin degradation with an expected increase in the patient compliance.
Keywords: Insulin, Liposomes, Sustained release, Topical spray, Factorial design.